Effect of spatial variability on performance of cement-treated soil slab during deep excavation. (10th November 2018) - Pan, Yutao; Shi, Guicai; Liu, Yong; Lee, Fook-Hou
Highlights: Spatial variability has adverse effect on performance of cement-treated soil slab. The reduction ratio on critical excavation depth from homogeneous condition is greater with wider, thinner CSSL and larger COV of strength. A rational approach for design of cement treated soil slab (CSSL) assuming the CSSL is homogeneous was proposed. Abstract: This study aims at investigating the effect of spatial variability on the short-term undrained performance of cement-treated soil slab during excavation and providing a rational design approach assuming the slab is homogeneous. The cement treated soil was simulated using an effective stress model. Deterministic analyses were first conducted to investigate the failure mechanism and failure criterion for different dimensions of cement-treated soil slab (CSSL). Random finite element method is then applied to consider the effect of spatial variability on performance of the CSSL. A rational design approach for CSSL is proposed to facilitate design which is usually conducted assuming the CSSL is homogeneous.